A New Method for Measuring the Angle of Hallux Valgus - Rahmat allah Heidarpour; Morteza Abdiani (The Society of Aging and Physical Activity (SAPA), 2017)
Objectives. The aim of this study is to introduce a new way and assign its reliability and validity in measuring the angle of hallux valgus. Methods. In this method, we have proceeded to introduce a simple way for measuring the angle of hallux valgus by using ruler and mathematical formulas. For doing this study, we selected 25students and measured their angle of hallux valgus with new way and by goniometer. To assign the reliability and validity, it has been used of correlation coefficient and ICC coefficient, respectively. Results. Findings show that, there is a significant correlation between new method and using goniometer (r=0/825). Besides, this method is of the high reliability for measuring the angle of hallux valgus (ICC=0/992). Conclusion. The new method not only is both cheap and simple measuring for measuring the angle of hallux valgus, but also have high reliability and validity.